Shorter delay to treatment by integrated diagnostic services and NGO- provided support among breast cancer patients in two Brazilian referral centres - Lorena Sofia dos Santos Andrade; Tácila Thamires de Melo Santos; Milena Edite Case de Oliveira; Kedma Anne Lima Gomes; Adriana Raquel Araújo Pereira Soares; Tiago Almeida de Oliveira; Mathias Weller (SAGE Publishing, 2021)
Background: The diagnosis of breast cancer requires a complicated series of diagnostic exams. The present study addressed the delay of patients who used publicly and privately financed diagnostic services. Non-governmental organizations (NGOs) donated diagnostic mammograms and biopsies. Design and Methods: Data from 304 patients were obtained from two Brazilian referral centres. In one referral centre (FAP), diagnostic mammography, clinic-histopathological exam and immunohistochemistry were outsourced, whereas in the other centre (HNL), these services were integrated. Cox regression, Kaplan-Meier analysis and non-parametric tests were used to compare variables and time intervals. Results: If diagnostic mammography was financed privately and covered by private health insurance, the likelihood of a delay of >90 days between the first medical visit and the initiation of treatment decreased 2.15-fold (95%CI: 1.06- 4.36; p=0.033) and 4.44-fold (95%CI: 1.58-12.46; p=0.004), respectively. If the clinic-histopathological exam was outsourced (FAP) and publicly or privately financed, the median time between diagnostic mammography and the diagnostic result was 53 and 65 days in the integrated (HNL) and outsourced public system, compared to 29 days in the outsourced private system (p<0.050). The median time between the first medical visit and the diagnostic results of patients who were supported by NGOs, who financed their diagnostic services privately, and who used exclusively public diagnostic services was, respectively, 28.0, 48.5 and 77.5 days (p<0.050). Conclusion: Patients who used privately financed health services had shorter delays. Compared to outsourcing, the integration of the publicly financed clinic-histopathological exam diminished the delay. The support of patients by NGOs accelerated patient flow.